Light In The Dark Azyumardi Azra's Cotribution In Framing Novelty of Nusantara Islam - Martinus Joko Lelono (P3TK, Sanata Dharma University, 2023)
Azyumardi Azra significantly contributed to re-framing the Indonesian situation during his lifetime as a scholar. This article works on the literature review of the works of Azra. It aims to perform an analytical article that helps people comprehend that social reality lives in certain identity politics. Azra proposed to look at reality from the